Neurodegenerations are diseases of the present and the future - Górska, Ewelina; Bogdan, Sylwia; Gorodkiewicz, Ewa; Hermanowicz, Adam (Journal of Education, Health and Sport, 2022)
Neurodegenerations are diseases of the present and the future. As the human population grows, the number of people suffering from neurodegenerative diseases will increase. Neurodegenerations diseases are Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, spinocerebellar ataxia, spinal muscular ataxia), sporadic (amyotrophic lateral sclerosis) or infectious (prion disease). Nerve cells (neurons) can’t regenerate and therefore die under the influence of pathological factors. Neurodegenerations diseases can be serious or life-threatening. It depends on the type. Drags and treatments may help improve symptoms, relieve pain, and increase mobility.